Structural Equation Modeling Based on Variance The Density Index of Larvae of The Rainy Season in the City of Banjarbaru - Isnawati Isnawati; Bambang Widjanarko Otok; Suharto Suharto; Arief Wibowo (CAUCHY: Jurnal Matematika Murni dan Aplikasi, 2018)
Climate change causes changes rainfall, temperature, air humidity and wind direction so that affect the reproduction of vectors of diseases such as the mosquito Aedes, Malaria, etc. that it needs to be monitored the increase in many cases DB. free number of larvae (ABJ) is one of the larva density indicator, although ABJ has more than 90 percent but morbidity remains high. The condition of the ABJ not describes the density of larvae jentik, so that the need to study the density jentik indicator that more can describe as the larvae density index with SEM based Variance approach. The results of the study showed that the structural model nonparametric to larva density is the best model based on the criteria of R2 and Q2. The Ministry of Health and behavior, environment condition and breeding place/site effect on the larva density of 87.7%. The dominant indicator counseling on health services, knowledge on the behavior of the temperature of the water on the conditions in the environment and the material container on the breeding place/sites. While on the larva density each indicator provides value loading, larvae density index (0.864), House index (0.459), Container index (0.894), and Breateau index (0.925). Environmental conditions the dominant factor in affecting larva density decline of 32.4%, with each indicator larvae density index (28%), House index (15%), Container index (29%), and Breateau index (30%).